Association of Self-Reported Disease Severity with Depression and Anxiety among COPD Patients - Yousef Saad Aldabayan; Antonieto Alaban; Eduardo Fabella; Amal Ismael Abdelhameed (Makara Journal of Health Research)
Background: This study was conducted to estimate the proportion of patients who experience a high impact from chronic obstructive pulmonary disease (COPD) on their health status and those who also experience symptoms of depression and anxiety. It also sought to determine whether the health impact of the disease is associated with anxiety and depression.